Analysis of Factors Affecting the Readability of Sustainability Reports on Companies Listed on the Indonesia Stock Exchange and Bursa Malaysia - Sri Mulyati; Silpia Eka Fitri Patonah (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
This study was conducted to determine the factors that can affect the readability of sustainability reports, especially in coal subsector mining companies listed on the Indonesia stock exchange and the Malaysian stock exchange in 2021-2023 that have published financial statements during the research period. The technique in determining the sample is using the purposive sampling method. Hypothesis testing in this study uses SPSS Version 25. The results of this study show that the variables of green governance quality measured based on board size, independent board, gender diversity, chief sustainability officer and sustainability committee, as well as shareholder pressure variables measured by ownership structure consectration partially have no effect on the readability of sustainable reports. Meanwhile, the sustainable economic performance variable measured by ROSI has a positive effect on the readability of the Sustainable Report. However, simultaneously these variables affect the readability of the continuous report.